Structural basis for arginine glycosylation of host substrates by bacterial effector proteins. Issue 1 (December 2018) - Park, Jun; Kim, Young; Yoo, Youngki; Kim, Juyeon; Jun, Sung-Hoon; Cho, Jin; El Qaidi, Samir; Walpole, Samuel; Monaco, Serena; García-García, Ana; Wu, Miaomiao; Hays, Michael; et al.
Abstract The bacterial effector proteins SseK and NleB glycosylate host proteins on arginine residues, leading to reduced NF-κB-dependent responses to infection.Salmonella SseK1 and SseK2 areE. coli NleB1 orthologs that behave as NleB1-like GTs, although they differ in protein substrate specificity. Here we report that these enzymes are retaining glycosyltransferases composed of a helix-loop-helix (HLH) domain, a lid domain, and a catalytic domain. A conserved HEN motif (His-Glu-Asn) in the active site is important for enzyme catalysis and bacterial virulence. We observe differences between SseK1 and SseK2 in interactions with substrates and identify substrate residues that are critical for enzyme recognition. Long Molecular Dynamics simulations suggest that the HLH domain determines substrate specificity and the lid-domain regulates the opening of the active site. Overall, our data suggest a front-face SN i mechanism, explain differences in activities among these effectors, and have implications for future drug development against enteric pathogens. The type III secretion system effectors NleB and SseK are glycosyltransferases (GT) that specifically glycosylate arginine residues. Here the authors provide insights into their mechanism by combining X-ray crystallography, NMR, enzyme kinetics measurements, molecular dynamics simulations and in vivo experiments and show that SseK/NleB enzymes are retaining GTs.